Dry Matter Content, Starch Content and Starch Yield Variability and Stability of Potato Varieties in Amhara Region of Ethiopia - Abebe, Tesfaye; Wongchaochant, Shermarl; Taychasinpitak, Thunya; Leelapon, Oranuch (Agriculture and Natural Resources, 2012)
Evaluation of dry matter content (DMC), starch content (SC) and starch yield (SY) of 25 potato varieties was carried out at three distinct locations in the Amhara region of Ethiopia during the 2011 cropping season. The main objectives were to examine the variability and stability of these traits and determine the proper production environments. The 25 varieties were examined in a complete 5 × 5 lattice design with six replications. Statistical analyses of the DMC, SC and SY of these varieties revealed signiﬁ cant (P < 0.01) genotypic and location variation and genotype × environment interactions. Consequently, their DMC and SC ranged from 17.82 to 26.70 and 9.75 to 17.85%, respectively, while SY ranged from 2.21 to 6.91 t.ha-1. Correlation analysis revealed a strong linkage (P < 0.01) among these characters. Additive main effects and multiplicative interactions analysis for DMC and SC stability identiﬁ ed Gorebella, Ater Abeba, Challa, Belete and CIP-396004.337 as relatively stable for processing while Menagesha, Bulle, Ararsa were suitable for table purposes. Furthermore, Debretabor followed by Adet were found suitable for producing processing types while Merawi was suitable for table types. Thus, this study distinctly separated varieties and environments on the one hand and the available genetic resources for a breeding program aimed at improving DMC and SY of potato in Ethiopia on the other.